Knowledge, attitudes, and practices of women related to human and animal feces management in Ethiopia: Evidence for strengthening water, sanitation, and hygiene (WaSH) initiatives - Hadush, B.; Fikru, C.; Kebede, G.; Guesh, S.; Kassaye, E.; Redae, G.; Amenu, Kebede; Cavalerie, Lisa; Mor, Siobhan M. (Elsevier, 2026)
Background: Water, sanitation, and hygiene (WaSH) programs aim to prevent feco-oral disease transmission, but their effectiveness in low- and middle-income countries is often compromised by frequent exposure to animal feces. In Ethiopia, national initiatives such as the Health Extension Program and Community-Led Total Sanitation and Hygiene program have expanded WaSH coverage but do not currently address animal-associated risks. This study investigated knowledge, attitudes, and practices related to human and animal feces management in Butajira, Gilgel Gibe, and Kilite Awlaelo Health and Demographic Surveillance Sites (HDSS) in Ethiopia.